TRPM6 N-Terminal CaM- and S100A1-Binding Domains - Zouharova, Monika (Int J Mol Sci, 2019)
Transient receptor potential (TRPs) channels are crucial downstream targets of calcium signalling cascades. They can be modulated either by calcium itself and/or by calcium-binding proteins (CBPs). Intracellular messengers usually interact with binding domains present at the most variable TRP regions—N- and C-cytoplasmic termini. Calmodulin (CaM) is a calcium-dependent cytosolic protein serving as a modulator of most transmembrane receptors. Although CaM-binding domains are widespread within intracellular parts of TRPs, no such binding domain has been characterised at the TRP melastatin member—the transient receptor potential melastatin 6 (TRPM6) channel. Another CBP, the S100 calcium-binding protein A1 (S100A1), is also known for its modulatory activities towards receptors. S100A1 commonly shares a CaM-binding domain. Here, we present the first identified CaM and S100A1 binding sites at the N-terminal of TRPM6. We have confirmed the L520-R535 N-terminal TRPM6 domain as a shared binding site for CaM and S100A1 using biophysical and molecular modelling methods. A specific domain of basic amino acid residues (R526/R531/K532/R535) present at this TRPM6 domain has been identified as crucial to maintain non-covalent interactions with the ligands. Our data unambiguously confirm that CaM and S100A1 share the same binding domain at the TRPM6 N-terminus although the ligand-binding mechanism is different.